Searching for common threads in threadfins: Phylogeography of Australian polynemids in space and time - Horne, J.; Momigliano, P.; Welch, D.; Newman, Stephen; Van Herwerden, L. (Inter-Research, 2012)
Proper management of marine fisheries requires an understanding of the spatial and temporal dynamics of marine populations, which can be obtained from genetic data. While numerous fisheries species have been surveyed for spatial genetic patterns, temporally sampled genetic data is not available for many species. We present a phylogeographic survey of the king threadfin Polydactylus macrochir across its species range in northern Australia and at a temporal scale of 1 and 10 yr. Spatially, the overall AMOVA fixation index was f st = 0.306 (F ' st = 0.838), p < 0.0001 and isolation by distance was strong and significant (r 2 = 0.45, p < 0.001). Temporally, genetic patterns were stable at a time scale of 10 yr. However, this did not hold true for samples from the eastern Gulf of Carpentaria, where populations showed a greater degree of temporal instability and lacked spatial genetic structure. Temporal but not spatial genetic structure in the Gulf indicates demographic interdependence but also indicates that fishing pressure may be high in this area. Generally, genetic patterns were similar to another co-distributed threadfin species Eleu - theronema tetradactylum, which is ecologically similar. However, the historical demography of both species, evaluated herein, differed, with populations of P. macrochir being much younger. The data are consistent with an acute population bottleneck at the last glacio-eustatic low in sea level and indicate that the king threadfin may be sensitive to habitat disturbances. © 2012 Inter-Research.